2017
DOI: 10.1515/raon-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Cancer burden in slovenia with the time trends analysis

Abstract: BackgroundThe aim of our study was to describe cancer burden and time trends of all cancers combined, the most frequent as well as the rare cancers in Slovenia.Patients and methodsThe principal data source was the population-based Cancer Registry of Republic of Slovenia. The cancer burden is presented by incidence and prevalence for the period 1950–2013 and by mortality for years 1985–2013. The time trends were characterized in terms of an average annual percent change estimated by the log-linear joinpoint reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 12 publications
3
71
0
Order By: Relevance
“…This study showed that the disease burden of cancer was mainly on people aged from 50 to 70. Vesna Zadnik et al found that the main financial burden—which increased with age—was on the elderly population and for both male and female, cancer was predominant in people aged from 50 to 74,21 presenting results similar to ours. However, for cancer control in the future, cancer prevention and control measures cannot be carried out only among the elderly population.…”
Section: Discussionsupporting
confidence: 87%
“…This study showed that the disease burden of cancer was mainly on people aged from 50 to 70. Vesna Zadnik et al found that the main financial burden—which increased with age—was on the elderly population and for both male and female, cancer was predominant in people aged from 50 to 74,21 presenting results similar to ours. However, for cancer control in the future, cancer prevention and control measures cannot be carried out only among the elderly population.…”
Section: Discussionsupporting
confidence: 87%
“…Locally advanced non-small cell lung cancer (LA-NSCLC) patients represent one third of all patients with NSCLC. 1 Approximately 70% of NSCLC patients in stage III have inoperable disease. Standard treatment for these patients is concurrent chemoradiotherapy (CCRT).…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma incidence is on the 6 th place among all the cancers in Slovenia and it is constantly rising during last period. 1 , 2 Although early melanoma has a good prognosis, melanoma with distant metastasis carries a high mortality rate. 3 Until recently there was a lack of successful treatment approach in metastatic melanoma.…”
Section: Introductionmentioning
confidence: 99%